Catalytic Microwave Pyrolysis of Albizia Branches Using Iraqi Bentonite Clays - Abd, Maha F.; Al-yaqoobi, Atheer M.; Abdul-Majeed, Wameath S. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Catalytic microwave-assisted pyrolysis of biomass is gaining popularity as an alternative to fossil fuels due to health, environmental, climate, and economic issues. This study conducted a catalytic pyrolysis process of the Albizia plant's branches using an Iraqi clay catalyst (bentonite) focusing on the variables including the biomass-particle size, experimental time, microwave power level, and the catalyst-to-biomass ratio. The physical and chemical properties of the resulting biofuel were analyzed presented by HHV, acidity, density, viscosity, GC-MS, FTIR for bio-oil and SEM, EDX, BET, HHV, FTIR for biochar. The study revealed that addition of bentonite as a catalyst led to enhanced production of biogas produced from 5% to 45% and decreased the power level used from 700 W to 450 W. Also, it raised the production of bio-oil generated with less power level and duration time. The addition of catalyst also affected the characteristics of bio-oil produced such as reducing the acidity by increasing its pH from 5 to 5.7, lowering the viscosity from 4.8 to 3.3 cSt, and the density from 1045 to 1039.2 kg/m3. Adding catalyst increased the percentage of aromatic and alcoholic substances in the bio-oil which led to improve the calorific value from 19.5 to 23 MJ/kg. Additionally, the biochar properties also improved, where the surface area and pore volume increased from 0.5512 to 40.384 m2/g and 0.00011 to 0.0361cm3/g respectively. The higher heating value was raised from 23.5 to 25 MJ/kg also. CH4 is also increased from 3.6 to 8.6% which is one of the essential fuel gasses.